Lymphangioma of the Ileocecal Valve Clinically Masquerading as a Submucosal Small Intestinal Gist: Report of a Case and Literature Review - Al-Obeed, Omar A. (Medknow Publications & Media Pvt Ltd, 2014)
Lymphangiomas are rare tumors affecting the gastrointestinal tract, and may be seen in the bowel, gall bladder, and pancreas. They resemble hemangiomas, but consist of spaces of variable sizes containing lymph. In this report, we describe the case of a 53-year-old male who presented with abdominal pain and constipation. Computerized tomography (CT) scan showed a polypoidal lesion at the ileocecal valve which was thought to be a gastrointestinal stromal tumor. Resected specimen did, however, show a lymphangioma. We also describe the clinicopathologic features of gastrointestinal lymphangiomas with a literature review.